THE INCLUSION OF AFFECTIVE VALUE INTO ENGLISH TEXTS IN TEACHING READING (An Experimental Study at Tenth Grades of SMA NW Pancor In The School Year 2010) - Muhammad Husnu (Universitas Hamzanwadi, 2010)
This research is aimed at finding out whether: The purpose of this research is to find out to what extent that the English texts that included in affective value effective in teaching reading at tenth grades of SMA NW Pancor in the school year 2012-2013The method which was applied in this research was experimental study. It was conducted at the tenth grades of SMA NW Pancor. The population of the research is tenth grades of SMA NW Pancor in the academic year of 2010. The samples were two classes. In taking the sample, a cluster random sampling technique was used. Each class was divided into two groups. Then, the techniques which were used to collect the data were a multiple choice test for getting the data of the students’ reading skill. The instruments were tried out to get valid and reliable items. T-test was used to analyze whether the alternative hypothesis is accepted or not.The statistical analysis had described that mean of the experimental group on pre-test is 12.87 and mean score on post-test is 16.06. Meanwhile, mean score of the control group on pre-test is 13.09 and mean score on post-test is 14. By using t-test at the level of significance (a) 0.05, the researcher got t-test t-table, that is 6.18 2.00, it means that there was a significant difference between the students’ reading comprehension before and after students were taught by using the English texts that included in affective value. Besides in the hypothesis testing, the result showed that the students’ achievement on posttest at experimental group was categorized into high rank. Meanwhile, the control group on posttest was categorized into average. It can be concluded that the English texts that included in affective value as a media was effective in teaching reading. Based on the findings, it can be concluded that in general the English texts that included in affective value is more effective than the conventional texts to teach reading.In accordance with the above result, the English teacher is expected to be able to select the appropriate teaching media to teach reading for their students. Key Words: affective value, English text, and Teaching Reading